2006
DOI: 10.1002/neu.20301
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in cell proliferation in the auditory midbrain of the bullfrog, Rana catesbeiana

Abstract: We examined patterns of cell proliferation in the auditory midbrain (torus semicircularis) of the bullfrog, Rana catesbeiana, over larval and early postmetamorphic development, by visualizing incorporation of 5-bromo-2'-deoxyuridine (BrdU) in cycling cells. At all developmental stages, BrdU-labeled cells were concentrated around the optic ventricle. BrdU-labeled cells also appeared within the torus semicircularis itself, in a stage-specific manner. The mitotic index, quantified as the percent of BrdU-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In the rat cortex, this protein is expressed only transiently during development, and is 'almost undetectable' in the adult. In the bullfrog brainstem, TOAD-64 is also expressed during development Simmons et al, 2006], but, in contrast to the rat cortex, it remains detectable in adults [this study]. This continued presence of TOAD-64 label lends support to the contention that the adult bullfrog brain contains early postmitotic neurons.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In the rat cortex, this protein is expressed only transiently during development, and is 'almost undetectable' in the adult. In the bullfrog brainstem, TOAD-64 is also expressed during development Simmons et al, 2006], but, in contrast to the rat cortex, it remains detectable in adults [this study]. This continued presence of TOAD-64 label lends support to the contention that the adult bullfrog brain contains early postmitotic neurons.…”
Section: Discussionsupporting
confidence: 62%
“…These authors suggested that birth of new cells occurs in the striatum but that these cells do not survive. Simmons et al [2006] estimated the percentages of double-labeled cells in the TS of recently metamorphosed froglets surviving 30 days post-BrdU injection to be approximately 20% (BrdU-GFAP) and 10% (BrdU-TOAD-64). These estimates in the froglet TS are within the same general range as those obtained in the adult TS at a similar survival time [this study].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, our data show some parallels between GAP-43 immunoreactivity and periods of cell proliferation in both the SON and the TS. Both of these brainstem nuclei show peaks of cell proliferation, as indexed by increased numbers of cells labeled with BrdU, during metamorphic climax Simmons et al, 2006], the time period during which GAP-43 expression is also intense. A subset of these newly-born cells might form processes, and the formation of these processes might be reflected in increased GAP-43 expression.…”
Section: Possible Correlates With Developmental Changes In Functionmentioning
confidence: 99%
“…The nervous system of the bullfrog undergoes more dramatic changes over development than those seen in Xenopus , particularly in auditory/vestibular pathways, and thus we might expect dramatic changes in GAP-43 expression, as indexed by changes in intensity and distribution of immunolabeling, during bullfrog metamorphosis. We hypothesized that changes in expression in the auditory medulla and midbrain, areas which we have previously shown to undergo considerable anatomical and physiological changes over development [Boatright-Horowitz and Simmons, 1997;Chapman et al, 2006;Simmons et al, 2006;Horowitz et al, 2007a, b], would correlate with patterns of GAP-43 immunoreactivity. Further, we examined patterns of GAP-43 immunoreactivity in selected cranial nerves and in the forebrain, to determine if any changes in expression reflect a general process of growth and reorganization affecting the entire brain simultaneously, or if certain patterns of expression are temporally or spatially specific.…”
Section: Introductionmentioning
confidence: 99%